2020
DOI: 10.1002/alz.042738
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of young onset dementia: A systematic review and meta‐analysis

Abstract: Background Onset of dementia before the age of 65 years is usually referred to as young onset dementia (YOD). Out of the total prevalence of dementia, it is estimated that 6‐9% are accounted for by YOD, but data to build robust estimates on is very limited in this specific dementia subgroup. Valid epidemiological data on the prevalence of people with YOD is needed to adequately provide dedicated services and care. This systematic review aimed to collate data from published literature and estimate the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 0 publications
5
67
1
1
Order By: Relevance
“…We did not identify any recommendations related to pregnancy and maternity. This is not surprising as it is rare for people with dementia to be young enough to be pregnant as most people with young-onset dementia are over 50 [ 88 ]. We found no recommendations related to marriage and civil partnership.…”
Section: Discussionmentioning
confidence: 99%
“…We did not identify any recommendations related to pregnancy and maternity. This is not surprising as it is rare for people with dementia to be young enough to be pregnant as most people with young-onset dementia are over 50 [ 88 ]. We found no recommendations related to marriage and civil partnership.…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis, the heterogeneity between studies was substantial, with many analyses showing I 2 > 80%. Previous meta-analyses on prevalence studies have reported similar results (65,66). The subgroup analyses failed to determine the reasons for this significant heterogeneity.…”
Section: Discussionmentioning
confidence: 92%
“…Experiences in the Netherlands are that service providers are also hesitant to design services for a "new" target group, because of the initial increase in costs that accompany the development of dedicated services. Also, the fact that the target group of these services is only an approximate 5% of all people living with dementia 11 probably further raises barriers for the establishment of such services.…”
Section: Service Provision In Young-onset Dementiamentioning
confidence: 99%
“…Based on a recent meta-analysis of international prevalence studies, estimates can be made that currently 14,000 to 17,000 people live with young-onset dementia in the Netherlands. 11 Because of the low prevalence, in the Netherlands postdiagnostic care and support in young-onset dementia is organized at the regional level with a hub-and-spoke approach in which one of the larger health care organizations together with smaller local partners offer services and support after the diagnosis. Guidelines and care standards are developed at the national level.…”
Section: Service Provision In Young-onset Dementiamentioning
confidence: 99%